Therapeutic Potential of Stem Cells in Follicle Regeneration - Agnieszka Owczarczyk-Saczonek; Magdalena Krajewska-Włodarczyk; Anna Kruszewska; Łukasz Banasiak; Waldemar Placek; Wojciech Maksymowicz; Joanna Wojtkiewicz (Stem Cells International)
Alopecia is caused by a variety of factors which affect the hair cycle and decrease stem cell activity and hair follicle regeneration capability. This process causes lower self-acceptance, which may result in depression and anxiety. However, an early onset of androgenic alopecia is associated with an increased incidence of the metabolic syndrome and an increased risk of the cardiac ischaemic disease. The ubiquity of alopecia provides an encouragement to seek new, more effective therapies aimed at hair follicle regeneration and neoregeneration. We know that stem cells can be used to regenerate hair in several therapeutic strategies: reversing the pathological mechanisms which contribute to hair loss, regeneration of complete hair follicles from their parts, and neogenesis of hair follicles from a stem cell culture with isolated cells or tissue engineering. Hair transplant has become a conventional treatment technique in androgenic alopecia (micrografts). Although an autologous transplant is regarded as the gold standard, its usability is limited, because of both a limited amount of material and a reduced viability of cells obtained in this way. The new therapeutic options are adipose-derived stem cells and stem cells from Wharton’s jelly. They seem an ideal cell population for use in regenerative medicine because of the absence of immunogenic properties and their ease of obtainment, multipotential character, ease of differentiating into various cell lines, and considerable potential for angiogenesis. In this article, we presented advantages and limitations of using these types of cells in alopecia treatment.